Liver Stiffness Measurement in Psoriasis: Do Metabolic or Disease Factors Play the Important Role? - Jamrus Pongpit (2018)
© 2016 Jamrus Pongpit et al. Background. An increased prevalence of metabolic syndrome including nonalcoholic fatty liver disease (NAFLD) was reported in psoriasis. NAFLD can progress to nonalcoholic steatohepatitis and fibrosis. Transient elastography (TE) is a noninvasive liver fibrosis assessment. We evaluated the prevalence of significant liver fibrosis or high liver stiffness measurement (LSM) using the LSM cutoff over 7 kPa and its associated factors in psoriatic patients. Methods. Subjects underwent TE and ultrasonography. Univariate and multivariate analysis were performed for the associated factors. Results. One hundred and sixty-eight patients were recruited. Three patients were excluded due to TE failure. Mean BMI was 24.8 ± 4.7 kg/m2. NAFLD, metabolic syndrome, and diabetes were seen in 105 (63.6%), 83 (50.3%), and 31 (18.8%) patients. The total cumulative dose of methotrexate over 1.5 g was seen in 39 (23.6%) patients. Mean LSM was 5.3 ± 2.9 kPa. High LSM was found in 18 (11.0%) patients. Waist circumference (OR: 1.24; 95% CI: 1.11-1.38; P = 0.0002), diabetes (OR: 12.70; 95% CI: 1.84-87.70; P = 0.010), and AST (OR: 1.08; 95% CI: 1.02-1.16; P = 0.017) were associated with high LSM. Conclusion. 11% of psoriatic patients had significant liver fibrosis by high LSM. Waist circumference, diabetes, and AST level were the independent predictors.